Comparison of 131I activity measurements at the NCBJ RC POLATOM and the ENEA-INMRI linked to the BIPM SIR system. (April 2018) - Ziemek, T.; Capogni, M.; Ratel, G.; Broda, R.; Dziel, T.; Fazio, A.; Listkowska, A.
Abstract: A bilateral comparison between ENEA-INMRI (Italy) and NCBJ RC POLATOM (Poland) of 131 I-solution activity measurements was organized in the year 2015 and piloted by POLATOM, which provided the sources for the comparison. The 131 I master solution was standardized independently at both institutes by using Liquid Scintillation Counting and ionization chamber techniques. The 131 I master solution was then sent by POLATOM to the BIPM International Reference System (SIR). The comparison was registered as an EURAMET.RI(II)-K2.I-131 key comparison allowing the ENEA-INMRI result to enter in the SIR database. Highlights: Bilateral comparison of the activity concentration of 131 I solution. Use of three Liquid Scintillation Counting methods and Ionization Chambers. Instruments, methods and uncertainty budgets are detailed. Excellent agreement of the reported results. Good agreement within the uncertainties with the KCRV value obtained by SIR result.